Susceptibility of feline immunodeficiency virus/human immunodeficiency virus type 1 reverse transcriptase chimeras to non-nucleoside RT inhibitors. - Auwerx, J; Esnouf, R; De Clercq, E; Balzarini, J (2004)
To map the determinants of the lack of susceptibility of feline immunodeficiency virus (FIV) reverse transcriptase (RT) to anti human immunodeficiency virus type 1 (HIV-1) non-nucleoside RT inhibitors (NNRTIs), a variety of chimeric HIV-1/FIV RTs were constructed. The majority of chimeric RTs had an affinity (Km) for their natural substrates comparable with that of the wild-type HIV-1 and FIV RTs, but their catalytic efficacy was decreased. Whereas HIV-1 RT could be made entirely insensitive to NNRTIs by exchanging the amino acid sequence 97 through 205 of FIV RT, none of the reverse FIV/HIV-1 RT chimeras gained susceptibility to NNRTIs. The amino acids that are thought to be involved in NNRTI susceptibility and that are different from those in HIV-1 RT have also been introduced in FIV RT. These mutant RTs gained virtually no susceptibility to efavirenz or capravirine. Vice versa, when these HIV-1-specific amino acids were replaced by their FIV RT counterparts in HIV-1 RT, susceptibility to the NNRTIs was lost. Thus, replacing segments or substituting relevant amino acids in FIV RT by their HIV-1 RT counterparts did not suffice to make FIV RT sensitive toward NNRTIs and was often accompanied by a decrease or even total loss of polymerase activity. It is postulated that, in contrast to the results found for HIV-1/HIV-2 RT chimeras and supported by the crystal structure of HIV-2 RT, there exist significant differences in the structure and/or flexibility of FIV RTs that may prevent NNRTIs from interacting with the FIV RT.